2016
DOI: 10.1519/jsc.0000000000001324
|View full text |Cite
|
Sign up to set email alerts
|

Functional Movement Screening Performance of Brazilian Jiu-Jitsu Athletes From Brazil: Differences Considering Practice Time and Combat Style

Abstract: Boscolo Del Vecchio, F, Foster, D, and Arruda, A. Functional movement screening performance of Brazilian jiu-jitsu athletes from Brazil: differences considering practice time and combat style. J Strength Cond Res 30(8): 2341-2347, 2016-Brazilian jiu-jitsu (BJJ) is a grappling combat sport that athletes, lying (guard fighter) or kneeling (pass fighter) on the mat, attempt to force their opponents to submit. Brazilian jiu-jitsu practices may result in muscular imbalances, which increase the risk of injury. Inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
0
13
0
6
Order By: Relevance
“…These results also showed that FMS screening should be performed before the competition season. The FMS has used for predicting sport-related injuries in many sports (8)(9)(10)(11)(16)(17)(18)(19)(20). The FMS has been used to predict injury risk in adult male handball players, in a recently published study from Poland.…”
Section: Discussionmentioning
confidence: 99%
“…These results also showed that FMS screening should be performed before the competition season. The FMS has used for predicting sport-related injuries in many sports (8)(9)(10)(11)(16)(17)(18)(19)(20). The FMS has been used to predict injury risk in adult male handball players, in a recently published study from Poland.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to coaches and physical trainers, these data suggest that it is important to consider competition level during training session activities in some as well as include specific strength training programs in order to prevent muscle imbalance and weakness, particularly in novice athletes. Specific evaluation methods such as isokinetic dynamometers and motion assessment methods including Functional Movement Screening (FMS) may be applicable for physically assessing BJJ athletes 29 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the battery of testing load performance, a complex of 9 indices was calculated, on the basis of which such key factors of FF structure as anaerobic power, mobility and economy were differentiated in accordance with specially developed algorithm [27][28][29][30]. On the basis of formalized point assessment of indices, the general level of FF and the degree of development of studied structural properties were determined.…”
Section: Methodsmentioning
confidence: 99%